Breeding biology of the Creamy-bellied Thrush (Turdus amaurochalinus) in southeast Brazil - Batisteli, Augusto Florisvaldo; Costiuc, Mariana Yamamoto [UNESP]; Santieff, Isadora Zavan; Costa, Rosane Oliveira; Sarmento, Hugo; Pizo, Marco Aurelio [UNESP] (Taylor & Francis Ltd, 2020)
The description of life-history traits is a prerequisite to understand the complex patterns of bird biodiversity. However, most of the highly diverse Neotropical avifauna still lack basic information on their reproductive behavior. Here, we describe the breeding biology of the Creamy-bellied Thrush (Turdus amaurochalinus) in a periurban area of southeast Brazil. We found 67 nests between early September and December in 2017 and 2018. Nests were 3.8 +/- 1.9 m (mean +/- SD) above ground, in native plants (43.3%), exotic plants (43.3%), and anthropogenic structures (13.4%). Clutch size was 2.9 +/- 0.3 eggs, which were incubated exclusively by females during 75.6 +/- 18.1% of the time. Both sexes reared the nestlings, but females performed more feeding trips and removed more fecal sacs than males. Incubation and nestling periods lasted, respectively, 13.0 +/- 0.6 and 13.2 +/- 1.5 days. Overall nesting success according to Mayfield method was 31.6%, and predation was the major cause of nest failure (52.8%). We concluded that this species had higher nest attentiveness, shorter nestling period, and higher nest survival compared to other Neotropical thrushes. The use of exotic plants and anthropogenic structures as nesting substrate may enhance the settlement of this migratory thrush in human-modified areas.
Keywords: Neotropical; nesting behavior; Turdidae; songbird; urban bird